2014
DOI: 10.1007/s00330-014-3525-y
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted perinatal postmortem magnetic resonance imaging as a marker of postmortem interval

Abstract: ObjectiveTo evaluate perinatal body organ apparent diffusion coefficient (ADC) values at postmortem magnetic resonance imaging (PMMR) in order to evaluate postmortem changes.MethodsPostmortem diffusion-weighted imaging (DWI) of the thorax and abdomen were performed with diffusion gradient values b = 0, 500, and 1000 s/mm2 on 15 foetal and childhood cases (mean 33.3 ± 7.8 weeks gestation) compared to 44 live infants (mean age 75.5 ± 53.4 days). Mean ADC values were calculated from regions of interest (ROIs) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
2
15
1
2
Order By: Relevance
“…T-test results are shown in Figure 2.Average MD values were obtained from all organs in all cases and shown inFigures 3 respectively. Brain and solid organ MD values are comparable to those obtained in previous studies(6,7). Myocardium and psoas muscle were found to have the highest MD values(Figure 3).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…T-test results are shown in Figure 2.Average MD values were obtained from all organs in all cases and shown inFigures 3 respectively. Brain and solid organ MD values are comparable to those obtained in previous studies(6,7). Myocardium and psoas muscle were found to have the highest MD values(Figure 3).…”
supporting
confidence: 85%
“…We have demonstrated feasibility of using a multiband diffusion imaging sequence in the perinatal post mortem setting. This sequence allowed the acquisition of higher (isotropic) with gradient values of 0, 500, 1000 s/mm 3 (6,7,20). We also note that other published work often quotes ADC values, although it is frequently unclear whether a single direction or the average of three directions was measured.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other radiological methods for the PMI estimation have been investigated, such as MRI spectroscopy or PMMR diffusion in perinatal death, however these are labor-intensive and contrary to PMCT, PMMRI is often not available for postmortem scanning [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that liver and renal cortex ADC values were lower in PM cases than normal live infants, which may be related to different water content of different organs and their rate of autolysis or decomposition. 35 Lung ADC values were higher, likely to represent fluid accumulation in the lungs following death, since there is no signal obtained from normal aerated lung parenchyma in live infants. Interestingly, there was a significant correlation between lung ADC and post-mortem interval, which could be of interest in medicolegal cases.…”
Section: T2-w Body Imagingmentioning
confidence: 99%